Cave Passage Levels and the Correlation Between Cave Lenght, Dry Valley and Clungup River in Sendang Biru Karst Area, Malang - Indonesia - Mohammad Ainul Labib; Depi Priyono (Universitas Negeri Surabaya, 2025)
Karst topography has various forms such as dry valleys, cave passages and surface rivers. The condition of these karst features has dynamic development. The purpose of this study is to analyze the frequency of cave cave passages, dry valleys, and surface rivers to interpret the cave levels and the correlation between cave passage and surface rivers and dry valley in karst area. The method used in this research is analyzing and doing review of cave mapping data and the data collection of surface rivers and dry valleys taken by the help of DEMNAS, which then identified the existence of surface rivers and valleys. The cave lenght analysis was done by calculating the lenght in each segment elevation. The analysis used was correlation test using SPSS. The result of the search showed that Clungup river comes from karst area with recharge from karst springs. The dry valley at the research site connects to Krompyang cave. The existence of dry valley and surface river have similar profile. The cave passages develop in several elevations. The analysis of these three features showed that there were 4 level patterns developed in Karst area of Sendang Biru. While the results of the correlation test between dry valley and Clungup river showed a sig value = 0.000 which was sig value = 0.000 < 0.05 that indicated a correlation between the 2 features. However, the cave passage features have no connection with the Dry Valley and Clungup River